Cluster policy: Insights from the German leading edge cluster competition - Michael Rothgang; Uwe Cantner; Jochen Dehio; Dirk Engel; Michael Fertig; H. Graf; S. Hinzmann; E. Linshalm; M. Ploder; A. -M. Scholz; Stefan Töpfer (Journal of Open Innovation: Technology, Market, and Complexity, 2017)
With its Leading-Edge Cluster Competition (in German: Spitzencluster-Wettbewerb; LECC), the Federal Ministry of Education and Research (Bundesministerium für Bildung und Forschung, BMBF) is supporting innovation clusters in a nationwide contest for the first time. In three waves, 15 cluster initiatives were selected and provided with funds to support them on their way to becoming international leaders in their field of technology. This paper presents the results of empirical studies regarding several important aspects of the LECC. The analysis of network relations shows that the LECC's short-term goal of intensifying or enhancing networking between innovative stakeholders in the cluster regions has been achieved. At the same time, certain types of regional impulses of the LECC can already be observed, primarily an improved visibility of the Leading-Edge Cluster regions and enhanced regional R&D activity. When looking at causal programme effects, we find that the programme increases firm-level R&D expenditure, but also that the programme design influences the programme impulse, e.g. by promoting additional activities of SMEs.
Keywords: 650